Energy consumption of High Power MANET Using LVC - Dr.N. Sasirekha, K.Santhya (International Journal of Engineering and Computer Science, 2017)
A mobile ad hoc network (MANET) is a self-configuring, infrastructure-less network of mobile devices which is connected without any wires. In MANET the node can move in any direction independently.The main challenge in building a MANET is equipping each device to continuously maintain the information needed and to properly route traffic. So, these networks may operate by themselves or may be connected to the larger Internet. They may contain one or multiple and different transceivers between the nodes. Finally in a highly dynamic, autonomous topology. Vehicular Ad-hoc Networks (VANETs) are used cars and cars and roadside equipment. MANETS can be used for facilitating the collection of sensor data for data mining for a variety of applications such as air pollution monitoring and different types of architectures can be used for such applications.